Strategi Komunikasi Organisasi Motor XTC dalam Membangun Citra Positif di Masyarakat Kota Serang - Laksana, April; Ferdiana, Riska; Falah, Miftahul (ANTASENA: Governance and Innovation Journal, 2023)
The phenomenon of actions carried out by motorcycle organizations involves illegal racing activities that often disturb the public. The public's perception of the presence of motorcycle organizations is something very frightening. However, it is different from the XTC (Exalt to Creativity) motorcycle organization, which has obtained official legality and has become part of a community organization (Ormas), being one of the renowned and largest motorcycle organizations in Indonesia. This research employs a qualitative descriptive method. Discussion Results With the transformation of the XTC Motorcycle Organization into a community organization, various positive activity programs can contribute to the community. Although once viewed as a brutal motorcycle organization, the public does not need to worry about encountering the XTC organization because it is now heading towards a positive direction, with clear and more structured goals and is registered and recognized by the government.